Design And Fabrication Of A Microstrip Antenna For Airborne Synthetic Aperture Radar - Vetharatnam, Gobi (2003)
An antenna for airborne synthetic aperture radar(SAR) has been develop in Multimedia University. It is a C-Band microstrip patch antenna with a central frequency of 6GHz and a bandwidth of 168 MHz(SWR<1.5). This prototype antenna achieves the required performance specification and it can be used in an airborne synthetic aperture radar system, which is a current R&D Project under the Center for Applied Electromagnetics of the Multimedia University.